ANTIVIRAL ACTIVITY OF FABACEAE AND ASTERACEAE FLAVONOID COMPOUNDS AGAINST SARS-CoV-2 ON SPIKE PROTEIN, MAIN PROTEASE (Mpro) AND RNA DEPENDENT RNA POLYMERASE (RdRp) RECEPTORS WITH IN SILICO METHOD: ANTIVIRAL ACTIVITY OF FABACEAE AND ASTERACEAE FLAVONOID COMPOUNDS AGAINST SARS-CoV-2 ON SPIKE PROTEIN, MAIN PROTEASE (Mpro) AND RNA DEPENDENT RNA POLYMERASE (RdRp) RECEPTORS WITH IN SILICO METHOD - Lekal, Tresia; Kesuma, Dini; Azminah, Azminah (Pharmaceutical Journal of Indonesia, 2023)
This study was conducted to test the antiviral activity of flavonoid compounds of Fabaceae tribe (Clitoria ternatea, Caesalpinia sappan, Leucaena leucocephala, Indigofera tinctoria) and Asteraceae tribe (Eclipta prostrata, Artemisia vulgaris, Blumea balsamifera, Chromolaena odorata) against SARS-CoV-2 on spike protein, Mpro and RdRp receptors by molecular docking method in silico. The results of molecular docking with AutoDock Vina showed that the flavonoid compounds apigenin and juglanin (Leucaena leucocephala), semiglabrin and glabratephrin (Indigofera tinctoria), apigetrin (Eclipta prostrata), acacetin (Chromolaena odorata) had binding energies close to, equivalent and better than the original ligand and Comparator of each receptor.